Encapsulation of multi-stimuli AIE active platinum( ii ) complex: a facile and dry approach for luminescent mesoporous silica - Pasha, Sheik Saleem; Alam, Parvej; Sarmah, Amrit; Roy, Ram Kinkar; Laskar, Inamur Rahaman (RSC advances, 2016)
Luminescent materials have great potential in diverse applications in their solid state. Because these materials are subject to the aggregation-caused quenching (ACQ) effect, increasing attention is focused on synthesizing aggregation-induced emission (AIE) active materials to avoid the ACQ effect. Herein a new class of AIE active, excimeric platinum( ii ) complex, [Pt(C^N)(L 1 )(Cl)], 3 [C^N = 2-phenylpyridine; L 1 = N 1 -tritylethane-1,2-diamine] is reported. The complex 3 exhibited mechanofluorochromism (MFC) and thereby transformed into an orange-emitting complex, 3a , upon grinding. Crushing of 3 (or 3a ) with meso -structured silica produced a luminescent composite material, 3b , and thereby the AIE Pt( ii ) complex moved into the mesopores and the process signaled with a drastic change of emission color (yellow → green). The solid-state luminescent behaviour of these complexes was thoroughly studied. The photophysical properties were also supported by TD-DFT based theoretical study.